2020
DOI: 10.1002/ab.21927
|View full text |Cite
|
Sign up to set email alerts
|

Predicting rape events: The influence of intimate partner violence history, condom use resistance, and heavy drinking

Abstract: Sexual aggression perpetration is a public health epidemic, and burgeoning research aims to delineate risk factors for individuals who perpetrate completed rape. The current study investigated physical and psychological intimate partner violence (IPV) history, coercive condom use resistance (CUR), and heavy episodic drinking (HED) as prospective risk factors for rape events. Young adult men (N = 430) ages 21-30 completed background measures as well as follow-up assessments regarding rape events perpetrated ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Sexual assault perpetration research also does not consistently evaluate the type of relationship in which a sexual assault occurred (Bagwell-Gray et al, 2015). Thus while existing studies reflect lower rates of sexual IPV relative to other forms of IPV, the extant literature suggests that certain profiles of individuals — namely those engaging in sexual IPV — may be at greater risk of perpetrating severe psychological or physical IPV (Barker et al, 2018; Gulati et al, 2021). Far more research is also needed regarding cyber dating abuse, which Brem and colleagues (2019) found had been perpetrated by almost half their sample in the last 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual assault perpetration research also does not consistently evaluate the type of relationship in which a sexual assault occurred (Bagwell-Gray et al, 2015). Thus while existing studies reflect lower rates of sexual IPV relative to other forms of IPV, the extant literature suggests that certain profiles of individuals — namely those engaging in sexual IPV — may be at greater risk of perpetrating severe psychological or physical IPV (Barker et al, 2018; Gulati et al, 2021). Far more research is also needed regarding cyber dating abuse, which Brem and colleagues (2019) found had been perpetrated by almost half their sample in the last 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of young adult male drinkers who used condoms inconsistently, 30.8% reported engaging in CUR via emotional consequences, 23.4% engaged in deception, 9.0% engaged in condom sabotage, and 1.6% engaged in physical force to obtain condomless sex (Davis, Stappenbeck, et al, 2014). Other studies showed that 35.3%–42.6% reported that they had used at least one coercive CUR strategy since age 14 (Davis & Logan-Greene, 2012; Gulati et al, 2021). In contrast, a study on pregnancy coercion (i.e., engaging in coercive CUR specifically to impregnate a partner) showed somewhat lower rates of coercive CUR, in that 5.1% of participants removed a condom during sex when their partner did not want them to, while 7.7% convinced their partner to have sex without a condom when they did not want to (Dimenstein et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Misogynistic attitudes, inconsistent condom use, a greater number of sex partners, sexual sensation seeking, and negative condom attitudes were risk factors for more frequent coercive CUR engagement (Davis & Logan-Greene, 2012), while more positive condom attitudes and lower impulsivity and hostility toward women served as protective factors (Davis, Stappenbeck, et al, 2014). Additionally, engaging in coercive CUR was associated with past year psychological intimate partner violence and was predictive of completed rape behavior over a 3-month follow-up period (Gulati et al, 2021). Finally, men who had engaged in stealthing were more likely to have had an STI or an unplanned partner pregnancy (Davis, 2019), and stealthing was more common among racial/ethnic minority men and men who reported greater instances of binge drinking, cannabis use, or other illegal drug use (Bonar et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such coercive tactics may include emotional manipulation, deception, condom sabotage, and threatening or using physical force to obtain sex without a condom; in contrast, noncoercive CUR strategies include making a direct request to not use a condom, discussing the reduced sensitivity associated with condom use, and withholding sex if a condom is used (Davis, Stappenbeck, et al, 2014). Although both men and women may employ coercive CUR, men are 2–3 times more likely to self-report that they have done so (Davis, Stappenbeck, et al, 2014; Wegner et al, 2018), with up to 42.6% of men reporting that they had used at least one coercive CUR strategy during their lifetime (Gulati et al, 2021). This suggests that, like other forms of sexual aggression, the vast majority of coercive CUR is perpetrated by men (Fernández-Fuertes et al, 2018).…”
Section: Distal Trait-level Risk Factors Of Coercive Curmentioning
confidence: 99%